2006
DOI: 10.1002/gcc.20388
|View full text |Cite
|
Sign up to set email alerts
|

Overlay analysis of the oligonucleotide array gene expression profiles and copy number abnormalities as determined by array comparative genomic hybridization in medulloblastomas

Abstract: Combined analysis of gene expression array data and array-based comparative genomic hybridization data have been used in a series of 26 pediatric brain tumors to define up- and downregulated genes that coincide with losses, gains, and amplifications involving specific chromosome regions. Frequent losses were defined in chromosome arms 3q, 6q, 8p, 10q, 16q, 17p, and gains were identified in chromosome 7, and chromosome arms 9p and 17q. Amplification of a 2p region was seen in only one tumor, which corresponded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…The number of patients in many of these studies, however, was still relatively small, and the technique used to identify chromosome 17 abnormalities may have been suboptimal. In our series, the aCGH profiles unequivocally identify 17p -/17q + (16,22,28). However, despite 22% of tumors in this series showing involvement of chromosome 17, no statistically significant correlation between these abnormalities and overall survival was detected.…”
Section: Discussioncontrasting
confidence: 55%
“…The number of patients in many of these studies, however, was still relatively small, and the technique used to identify chromosome 17 abnormalities may have been suboptimal. In our series, the aCGH profiles unequivocally identify 17p -/17q + (16,22,28). However, despite 22% of tumors in this series showing involvement of chromosome 17, no statistically significant correlation between these abnormalities and overall survival was detected.…”
Section: Discussioncontrasting
confidence: 55%
“…This approach provides a more focused analysis which is less affected by random changes between tumors. We have recently developed a software tool which can perform this association between expression and CNAs on a genome-wide level (Lo et al, 2007a) and, when applied to a survey of gliomas, we have readily identified potential candidate genes for involvement in tumor development. As shown in frequent amplification events, not only are previously implicated genes over expressed, but in many cases the adjacent genes are equally, and often more prominently, over expressed as we described previously for amplicons involving the EGFR locus, for example (Rossi et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of the aCGH karyotypes described above provided a detailed survey of chromosome losses, gains and amplifications in the current series of GBM, and provided the substrate for the superimposition of the expression data using the RPCI Overlay Tool developed by Lo et al (2007a). Gene expression levels were established using the U133Plus2.0 arrays with RNA from the same 30 tumor samples used for the aCGH analysis.…”
Section: Expression Array Analysismentioning
confidence: 99%
See 2 more Smart Citations